Icephobic performance on the aluminum foil-based micro-/nanostructured surface - 陈宇 刘桂成 姜磊 金志永 叶锋 李重基 王磊 王波 (Chinese physics B, 2017)
The research of superhydrophobic materials has attracted many researchers＇ attention due to its application value and prospects.In order to expand the serviceable range,people have investigated various superhydrophobic materials.The simple and easy preparation method has become the focus for superhydrophobic materials.In this paper,we present a program for preparing a rough surface on an aluminum foil,which possesses excellent hydrophobic properties after the treatment with low surface energy materials at high vacuum.The resulting contact angle is larger than 160° and the droplet cannot freeze on the surface above-10 ℃.Meanwhile,the modified aluminum foil with the thickness of less than 100 μm can be used as an ideal flexible applied material for superhydrophobicity/anti-icing.